Intracellular Ca(2+)-handling differs markedly between intact human muscle fibers and myotubes - Olsson, Karl (Skelet Muscle, 2015)
BACKGROUND: In skeletal muscle, intracellular Ca(2+) is an important regulator of contraction as well as gene expression and metabolic processes. Because of the difficulties to obtain intact human muscle fibers, human myotubes have been extensively employed for studies of Ca(2+)-dependent processes in human adult muscle. Despite this, it is unknown whether the Ca(2+)-handling properties of myotubes adequately represent those of adult muscle fibers. METHODS: To enable a comparison of the Ca(2+)-handling properties of human muscle fibers and myotubes, we developed a model of dissected intact single muscle fibers obtained from human intercostal muscle biopsies. The intracellular Ca(2+)-handling of human muscle fibers was compared with that of myotubes generated by the differentiation of primary human myoblasts obtained from vastus lateralis muscle biopsies. RESULTS: The intact single muscle fibers all demonstrated strictly regulated cytosolic free [Ca(2+)] ([Ca(2+)](i)) transients and force production upon electrical stimulation. In contrast, despite a more mature Ca(2+)-handling in myotubes than in myoblasts, myotubes lacked fundamental aspects of adult Ca(2+)-handling and did not contract. These functional differences were explained by discrepancies in the quantity and localization of Ca(2+)-handling proteins, as well as ultrastructural differences between muscle fibers and myotubes. CONCLUSIONS: Intact single muscle fibers that display strictly regulated [Ca(2+)](i) transients and force production upon electrical stimulation can be obtained from human intercostal muscle biopsies. In contrast, human myotubes lack important aspects of adult Ca(2+)-handling and are thus an inappropriate model for human adult muscle when studying Ca(2+)-dependent processes, such as gene expression and metabolic processes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13395-015-0050-x) contains supplementary material, which is available to authorized users.